Hydrogeological Analysis of Sulfide Tailings at a Uranium Mine Using Geophysical and Hydrochemical Methods - Targa, Débora Andrade [UNESP]; Moreira, César Augusto [UNESP]; Casagrande, Matheus Felipe Stanfoca [UNESP] (Springer Nature, 2021)
A hydrogeological analysis was conducted of aquifer systems within a sulfide-rich tailings pile and underlying rocks at a uranium mine to understand the generation and transport of AMD. A geophysical investigation was carried out along seven transects spaced 30 m apart using electrical resistivity tomography and a Wenner-Schlumberger array. The results were used as input to 2D and pseudo-3D models of resistivity and chargeability parameters. The geophysical results and models contrasted unaffected saturated zones and zones impacted by AMD, in addition to three areas within the tailings with a high sulfide content. The tailings and underlying fractured bedrock aquifer are hydrologically connected, which promotes the exchange of mine-influenced water into the regional aquifer. Releases from the site’s tailings and other wastes can severely affect regional groundwater.
Análisis hidrogeológico de relaves de sulfuro en una mina de uranio mediante métodos geofísicos e hidroquímicos
Keywords: Acid mine drainage; Brazil; Chargeability; Electrical resistivity tomography